Magnetic particle, magnetic particle for assay, and method for producing magnetic particle

By preparing magnetic particles of secondary particles and primary particles with a specific particle size range and forming a resin layer on the surface of the particles, the problems of ultra-paramagneticity and insufficient magnetization of magnetic particles when operating under an external magnetic field in the prior art are solved, and the ability to move and transport quickly under an external magnetic field and high working efficiency are achieved.

JP2025038884APending Publication Date: 2025-03-19CANON KK +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024151501
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-07
Filing Date
2024-09-03
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

When existing magnetic particles operate under external magnetic fields, it is difficult to realize magnetic particles that are both superparamagnetic and have large magnetization.

Method used

Magnetic particles with secondary particles, wherein the average particle size of primary particles is between 2 nm and 20 nm, the average particle size of secondary particles is between 500 nm and 5000 nm, and a resin layer is formed on the surface of the particles to improve operability.

Benefits of technology

The ability to quickly move and transport magnetic particles under external magnetic fields is realized, while improving working efficiency and being able to operate effectively in high viscosity solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038884000001_ABST
    Figure 2025038884000001_ABST
Patent Text Reader

Abstract

To provide magnetic particles that contain secondary particles in which a plurality of primary particles having particle diameters considered to have superparamagnetic property are aggregated, wherein the secondary particles have larger particle diameters.SOLUTION: Magnetic particles contain secondary particles in which a plurality of primary particles are aggregated, wherein an average particle diameter of the secondary particles is 500 nm or more and 5,000 nm or less, and an average particle diameter of the plurality of primary particles is 2 nm or more and 20 nm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to magnetic particles, magnetic particles for assays, and a method for producing magnetic particles. [Background technology]

[0002] Magnetic particles containing Fe3O4 are used in biomedical applications such as immunoassays, separation and purification of biomolecules, and drug delivery. Fe3O4 particles used in such biomedical fields need to be highly manipulable by external magnetic fields. The main magnetic properties of Fe3O4 particles, which are closely related to the manipulability by external magnetic fields, are remanent magnetization and saturation magnetization (hereinafter simply referred to as "magnetization"), which depend on the particle size of the Fe3O4 particles.

[0003] In order to easily control the aggregation and dispersion of Fe3O4 particles in a medium using an external magnetic field, it is necessary to reduce the remanence of the Fe3O4 particles, which is the magnetization when the application of the external magnetic field is stopped. It is known that the remanence of Fe3O4 particles decreases with decreasing particle size, and when the particle size is 20 nm or less, the remanence becomes zero, that is, the particles exhibit superparamagnetism.

[0004] Non-Patent Document 1 discloses an Fe3O4 cluster synthesized by adding sodium acrylate to an ethylene glycol solution of iron (III) chloride hexahydrate in order to reduce the size of the primary particles. Non-Patent Document 2 discloses an Fe3O4 cluster synthesized by adding trisodium citrate to an ethylene glycol solution of iron (III) chloride anhydride in order to reduce the size of the primary particles. Both of these Fe3O4 clusters are superparamagnetic because the primary particle size is 20 nm or less. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] S.Xuan, YXJWang, JCYu, KCFLeung, Chemistry of Materials, vol.21, p.5079-5087(2009). [Non-Patent Document 2] J. Liu, Z. Sun, Y. Deng, Y. Zou, C. Li, X. Guo, L. Xiong, Y. Gao, F. Li, D. Zhao, Angewandte Chemie International Edition, vol.48, p.5875-5879(2009). Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide magnetic particles which contain secondary particles which are aggregates of primary particles having a particle size considered to have superparamagnetism, the secondary particles having a larger particle size. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides A magnetic particle including a secondary particle formed by an aggregation of a plurality of primary particles, The average particle size of the secondary particles is 500 nm or more and 5000 nm or less, The magnetic particles are characterized in that the average particle size of the primary particles is 2 nm or more and 20 nm or less. The present invention also relates to magnetic particles for assay, comprising the above-mentioned magnetic particles and a resin layer on the outer side of the magnetic particles. The present invention also provides a method for producing a semiconductor device comprising the steps of: A method for producing magnetic particles including secondary particles formed by aggregation of primary particles, comprising the steps of: Obtaining an iron(III)-containing solution; Aging the iron(III)-containing solution; a step of obtaining a mixed solution by mixing the iron (III)-containing solution obtained in the aging step with a precipitating agent; heating the mixture; A method for producing magnetic particles comprising the steps of: Effect of the Invention

[0008] According to the present invention, it is possible to provide an Fe3O4 cluster that exhibits both superparamagnetism and large magnetization. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram of the structure of a magnetic particle (Fe3O4 cluster) according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a magnetic particle for assay according to an embodiment of the present invention. [Diagram 3] Synthesis flow of Fe3O4 clusters. [Figure 4] Synthesis flow of Fe3O4 clusters by blending method. [Diagram 5] SEM images of the Fe3O4 clusters produced in Example 1. (a) Low magnification, (b) High magnification. [Figure 6] SEM images of the Fe3O4 clusters produced in Example 2. (a) Low magnification, (b) High magnification. [Figure 7] SEM images of the Fe3O4 clusters produced in Example 6. (a) Low magnification, (b) High magnification. [Figure 8] SEM images of the Fe3O4 clusters produced in Example 8. (a) Low magnification, (b) High magnification. [Figure 9] SEM images of the Fe3O4 clusters produced in Example 14. (a) Low magnification, (b) High magnification. [Figure 10] SEM images of the generated Fe3O4 clusters. (a) Example 22, (b) Example 23, (c) Example 24, (d) Example 25, (e) Example 26, (f) Example 27, (g) Example 28, (h) Example 29. [Figure 11] SEM images of the Fe3O4 clusters produced in Comparative Example 2. (a) Low magnification, (b) High magnification. [Figure 12] SEM images of the Fe3O4 clusters produced in Comparative Example 3. (a) Low magnification, (b) High magnification. [Figure 13]SEM images of the generated Fe3O4 clusters. (a) Synthesis Example 1, (b) Example 30, (c) Example 31, (d) Example 32, (e) Synthesis Example 2. [Figure 14] XRD patterns of the produced particles: (a) Example 22, (b) Example 24, (c) Example 26, (d) Example 28. [Figure 15] Hysteresis curves of the particles produced: (a) Example 22, (b) Example 24, (c) Example 26, (d) Example 28. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The embodiment of the present invention will be described in detail. In the present invention, the term "Fe3O4 cluster" and "secondary particle" are synonymous.

[0011] [First embodiment] A first embodiment of the present invention is directed to magnetic particles. First, the problem in this embodiment will be described. In order to enable rapid movement or transportation of Fe3O4 particles in a medium by an external magnetic field in various tests using magnetic particles, such as an optical waveguide type test system described later, the Fe3O4 particles need to have a large magnetization. In general, the magnetization per particle of magnetic particles increases with increasing particle size. Therefore, by increasing the particle size of the Fe3O4 particles, the magnetization per particle of the Fe3O4 particles can be increased.

[0012] As described above, there is a trade-off between small particle size for superparamagnetism, which is a requirement for Fe3O4 particles that are highly manipulable by an external magnetic field, and large particle size for large magnetization, and it is therefore difficult to obtain Fe3O4 particles that are both superparamagnetic and large magnetization.

[0013] Fe3O4 clusters are known to be secondary particles consisting of multiple Fe3O4 primary particles of several tens of nanometers in size. By controlling the number of primary particles that are aggregated while keeping the primary particles of the Fe3O4 cluster small, in other words, by controlling the particle size of the secondary particles, it is possible to obtain Fe3O4 clusters that are both superparamagnetic and have large magnetization.

[0014] On the other hand, the Fe3O4 clusters produced by the methods of Non-Patent Documents 1 and 2 above are superparamagnetic because the primary particle size is 20 nm or less. However, the secondary particle size is a maximum of 280 nm in Non-Patent Document 1 and a maximum of 410 nm in Non-Patent Document 2, so the magnetization per particle of these Fe3O4 clusters is small. Therefore, these Fe3O4 clusters are not suitable for applications that require the magnetic particles to be moved or transported quickly in a medium by a magnetic field. In order to move or transport quickly in a medium by an external magnetic field, the Fe3O4 cluster needs to have a larger particle size.

[0015] The magnetic particles according to the embodiment of the present invention are A magnetic particle including secondary particles formed by aggregation of primary particles, The average particle size of the secondary particles is 500 nm or more and 5000 nm or less, The primary particles have an average particle size of 2 nm or more and 20 nm or less. According to the magnetic particles of this embodiment, it is possible to provide Fe3O4 clusters that are both superparamagnetic and highly magnetized. When used for assays, particularly immunoassays, it is possible to collect magnetic particles for assay in a solution in a shorter time than with conventional products, and the work efficiency can be significantly improved. In addition, it is possible to collect magnetic particles for assay even in a highly viscous solution, making it possible to perform immunoassays on highly viscous solutions. A detailed explanation is provided below.

[0016] The magnetic particles according to this embodiment are magnetic particles including secondary particles formed by aggregating a plurality of primary particles. The structure of the magnetic particle (Fe3O4 cluster) according to this embodiment is shown in FIG. 1. The secondary particles of the magnetic particle according to this embodiment preferably contain Fe3O4. The Fe3O4 cluster according to this embodiment is a secondary particle 12 formed by an assembly of a plurality of Fe3O4 primary particles 11. The secondary particles of the magnetic particle according to this embodiment preferably have a spherical shape. The shape of the Fe3O4 cluster is preferably spherical, depending on the application. In this embodiment (FIGS. 5, 6, 7, 8, 9, 10, 13, and 15), the term "sphere" refers to a substantial sphere such as a "round shape" or "ball-like shape," and is not limited to a perfect sphere. It also includes anisotropic spheres and spheres with partial dents or cracks. The shape of the Fe3O4 cluster according to this embodiment can be confirmed by observing the secondary particles with a scanning electron microscope (SEM).

[0017] As mentioned above, the magnetic properties of Fe3O4 clusters depend on the particle size of the primary particles (primary particle size) and the secondary particles (secondary particle size) of the Fe3O4 clusters. The remanence of the Fe3O4 clusters decreases with decreasing primary particle size, and when the primary particle size is 20 nm or less, the remanence is zero, that is, the clusters exhibit superparamagnetism. In addition, the number of primary particles that are aggregated, that is, the secondary particle size, correlates with the magnetization of the Fe3O4 clusters, and the magnetization of the Fe3O4 clusters increases with increasing secondary particle size. In other words, magnetic particles with larger secondary particle size have larger magnetization (e.g., saturation magnetization). Fe3O4 clusters in which primary particles are aggregated to have a particle size of 500 nm or more have large magnetization.

[0018] In the magnetic particles according to the present embodiment, the secondary particles preferably have superparamagnetic magnetism. The magnetic properties and magnetization of the secondary particles of the Fe3O4 clusters according to the present invention can be measured using, for example, a commercially available vibrating sample magnetometer (VSM) or a superconducting quantum interference device (SQUID).

[0019] The primary particle size and secondary particle size of the Fe3O4 cluster in this embodiment are number-average particle sizes measured from scanning electron microscope (SEM) images. For each of the examples and comparative examples, the average particle size of 50 primary particles randomly extracted from the SEM images of the prepared Fe3O4 clusters and the average particle size of the secondary particles were calculated. In addition, the median diameters D50 and D90 were calculated from the number-based particle size distribution measured by dynamic light scattering (DLS).

[0020] The magnetic particles according to this embodiment have an average secondary particle size of 500 nm or more and 5000 nm or less, and preferably an average secondary particle size of 500 nm or more and 3000 nm or less. The magnetic particles according to this embodiment have a secondary particle size (upper limit) of 5000 nm or less, preferably 4000 nm or less, more preferably 3000 nm or less, and even more preferably 2400 nm or less. The magnetic particles according to this embodiment have a secondary particle size (lower limit) of preferably 500 nm or more, more preferably 700 nm or more, even more preferably 800 nm or more, and particularly preferably 1000 nm or more. In this way, the magnetic particles can obtain a large magnetization (for example, a large saturation magnetization). For example, magnetic particles having twice the particle size (e.g., secondary particle size of 800 nm) of conventional particles (e.g., secondary particle size of 400 nm) can have approximately 8 times the saturation magnetization of conventional particles, and magnetic particles having 6 times the particle size (e.g., secondary particle size of 2400 nm) can have more than 200 times the saturation magnetization of conventional particles.

[0021] The magnetic particles according to this embodiment have an average primary particle size (average particle size) of 2 nm or more and 20 nm or less. The magnetic particles according to this embodiment have a primary particle size (upper limit) of 20 nm or less, preferably 19 nm or less, more preferably 18 nm or less, and even more preferably 16 nm or less. The magnetic particles according to this embodiment have a primary particle size (lower limit) of 2 nm or more, preferably 4 nm or more, more preferably 7 nm or more, even more preferably 10 nm or more, and particularly preferably 12 nm or more. In this way, the magnetic particles according to this embodiment have superparamagnetism and can have a residual magnetization of 0 (zero).

[0022] The secondary particles of the magnetic particles according to this embodiment typically contain Fe3O4, but may contain other iron oxides such as Fe2O3 and FeO within the range in which the effects of this embodiment can be obtained. In addition, the particles may be mixtures containing magnetic substances such as ferrite as well as simple substances. The secondary particles of the magnetic particles according to this embodiment are preferably Fe3O4. The magnetic particles according to this embodiment are preferably composed of only Fe3O4 clusters, and basically do not contain other compositions or structures, such as γ-Fe2O3. It can be confirmed by X-ray diffraction (XRD) that the magnetic particles are composed of only Fe3O4 and do not contain other substances such as γ-Fe2O3.

[0023] [Application example] An application example of this embodiment is a magnetic particle for assay. The magnetic particle for assay according to the embodiment of the present invention preferably has the magnetic particle according to this embodiment and a resin layer on the outside of the magnetic particle.

[0024] The magnetic particles for assay according to this embodiment will be described with reference to FIG. The assay magnetic particles 36 according to this embodiment preferably have a silica layer between the magnetic particles and the resin layer. The Fe3O4 clusters 31 serving as cores are covered with an inorganic substance layer 32.

[0025] To ensure the smoothness of the surface of the Fe3O4 cluster 31, the Fe3O4 cluster is coated with an inorganic layer 32. The inorganic layer 32 is preferably a silica layer. Silica is chemically stable, and a uniform and smooth layer can be formed on the surface of the Fe3O4 cluster 31 by a wet method such as the Stоber method. The outside of the inorganic layer 32 is coated with a resin layer.

[0026] In the assay magnetic particles according to this embodiment, the resin layer preferably includes at least a first resin layer 33 and a second resin layer 34. In the assay magnetic particles 36 according to this embodiment, the first resin layer 33 and the second resin layer 34 are formed on the outside of the inorganic substance layer 32. The first resin layer 33 is formed to protect the Fe3O4 clusters 31. For example, a silica layer formed by the Stоber method has a porous structure, and is therefore insufficient for chemical protection of Fe3O4. In the assay magnetic particles according to this embodiment, the first resin layer 33 is preferably a hydrophobic resin layer. The first resin layer 33 is preferably a styrene-based resin having high chemical stability and hydrophobicity.

[0027] In the assay magnetic particles according to this embodiment, the second resin layer 34 is preferably disposed outside the first resin layer 33, and the second resin layer 34 is preferably a polyglycidyl methacrylate layer. The assay magnetic particles 36 according to this embodiment preferably contain a ligand bound to the surface of the resin layer, and the ligand is preferably an antibody 35. The second resin layer 34 is provided to immobilize the antibody 35 on the outermost surface of the assay magnetic particles 36. Since a carboxyl group, an amino group, a thiol group, an epoxy group, etc. are suitable as functional groups for binding the antibody 35 to the outermost surface of the assay magnetic particles 36, the second resin layer 34 is preferably a resin containing these functional groups.

[0028] The magnetic particles for assay according to this embodiment may further contain a fluorescent material. There is no limitation on the method of applying the fluorescent material, and any known technology may be selected. The timing of applying the fluorescent material may be, for example, when the silica layer is formed, or before the silica layer is formed and the first resin layer is formed, or when the first resin layer is formed, the fluorescent material may be mixed together, or before the first resin layer is formed and the second resin layer is formed, or after the second resin layer is formed.

[0029] The method of providing the fluorescent material can be, for example, by mixing the fluorescent material with an organic solvent after forming the resin layer and stirring while heating, or by mixing the fluorescent material together when forming the resin layer. There is no limitation on the fluorescent material to be selected, and any known fluorescent material can be selected. The fluorescent material may be either non-polymerizable or polymerizable. Examples of non-polymerizable fluorescent materials include rhodamine B, rhodamine 6G, and europium complexes such as Lumesis (registered trademark) E-400 and Lumesis (registered trademark) E-460, while examples of polymerizable fluorescent materials include acryloxyethyl thiocarbamoyl rhodamine B and methacryloxyethyl thiocarbamoyl rhodamine B.

[0030] (Method of detecting antigens using magnetic particles in an optical waveguide type testing system) In an optical waveguide testing system, when detecting an antigen from a sample such as a specimen, magnetic particles bound to an antibody that specifically binds to the antigen and a sensor to which the antibody that specifically binds to the antigen is fixed are used. The sensor is placed below the direction of gravity, and an electromagnet that generates a magnetic force is placed near the sensor. When the electromagnet is activated, the magnetic particles can be attracted to the vicinity of the sensor by the action of gravity and magnetic force. Then, by utilizing the antigen-antibody reaction, the magnetic particles attracted to the vicinity of the sensor bind to the antibody provided on the sensor surface via the antigen. Furthermore, by placing an electromagnet above the direction of gravity, the magnetic particles that are not bound to the antibody provided on the sensor surface can be pulled up in the direction opposite to gravity. This makes it possible to separate the magnetic particles that are bound to the sensor from the magnetic particles that are not bound to it.

[0031] By measuring the change in the amount of outgoing light when light is incident on the sensor from a light source, it is possible to measure the presence, concentration, amount, etc. of magnetic particles bound to the sensor surface via an antigen-antibody reaction. In other words, when there are magnetic particles bound to the sensor surface (a lot), the amount of outgoing light is smaller than when there are no magnetic particles (a few). Therefore, it is possible to measure the presence, concentration, amount, etc. of the measurement target substance such as an antigen in a sample based on the amount of attenuation from the amount of outgoing light detected before the magnetic particles bind to the sensor.

[0032] When detecting a substance to be measured using such a method, it is important to reduce test errors by reducing non-specific adsorption of proteins other than the substance to be measured to the magnetic particles, and by reducing adsorption when there is no antigen on the sensor surface. For this purpose, a resin layer is formed on the surface of the magnetic particles. The resin layer is preferably hydrophilic, and contains functional groups that can bind ligands such as antibodies.

[0033] Second Embodiment The second embodiment of the present invention relates to a method for producing magnetic particles. The method for producing magnetic particles according to this embodiment aims to facilitate control of the primary particle size and secondary particle size. The method for manufacturing magnetic particles according to an embodiment of the present invention is a method for manufacturing magnetic particles including secondary particles in which a plurality of primary particles are aggregated, comprising a step of obtaining an iron(III)-containing solution, a step of aging the iron(III)-containing solution, a step of obtaining a mixed solution by mixing the iron(III)-containing solution obtained in the aging step and a precipitating agent, and a step of heating the mixed solution. It includes. According to the manufacturing method of the present embodiment, since it is easy to control the primary particle size and the secondary particle size, it is possible to provide a method for manufacturing magnetic particles that have superparamagnetism and have a wide range of magnetization according to the application (have a wide range of secondary particle sizes). The description will be given below.

[0034] The method for manufacturing magnetic particles according to the present embodiment is a method for manufacturing magnetic particles including secondary particles in which a plurality of primary particles are aggregated. As described above, the magnetic properties of Fe3O4 clusters depend on the primary and secondary particle sizes of the Fe3O4 clusters. The residual magnetization of the Fe3O4 clusters decreases as the primary particle size decreases, and when the primary particle size becomes 20 nm or less, the residual magnetization becomes zero, showing so-called superparamagnetism. Also, the number of aggregated primary particles, that is, the secondary particle size, is correlated with the magnetization of the Fe3O4 clusters, and the magnetization of the Fe3O4 clusters increases as the particle size increases. Therefore, if the particle size of the Fe3O4 clusters can be controlled, Fe3O4 clusters having a wide range of magnetization can be obtained. However, in the present embodiment, when the shape of the Fe3O4 clusters is deformed and bound or becomes amorphous, it is not included in the magnetic particles which are secondary particles in which a plurality of primary particles according to the present embodiment are aggregated. This is because in such a case, the secondary particles are in a state where they are further associated and cannot be said to be the secondary particles in the present embodiment.

[0035] <Synthesis of Fe3O4 clusters> The synthesis flow of the Fe3O4 cluster according to this embodiment is shown in Figure 3. The synthesis of the Fe3O4 cluster mainly comprises an iron (III)-containing solution preparation step (a step of obtaining an iron (III)-containing solution), a mixed solution preparation step (a step of obtaining a mixed solution), and a heating step (a step of heating the mixed solution), and includes an aging step (a step of aging the iron (III)-containing solution) as appropriate. Each step will be described in detail below.

[0036] <Step of Obtaining Iron(III)-Containing Solution> The method for producing magnetic particles according to this embodiment includes a step of obtaining an iron(III)-containing solution containing ethylene glycol and anhydrous iron(III) chloride, and preferably, the iron(III)-containing solution obtained in the step of obtaining an iron(III)-containing solution contains ethylene glycol and anhydrous iron(III) chloride. First, the preparation of the iron(III)-containing solution will be described. The iron(III)-containing solution is prepared by dissolving an iron(III) compound in ethylene glycol. As the iron(III) compound, anhydrous iron(III) chloride or iron(III) chloride hexahydrate is suitable.

[0037] These may be used alone or in any mixture in any ratio. In addition to iron(III) chloride, iron(III) nitrate, iron(III) acetate, iron(III) sulfate, ammonium iron(III) sulfate, iron(III) acetylacetonate, iron(III) hydroxide, iron(III) oxide, and hydrates thereof may be used alone or in a mixture of two or more. There is no limitation to these iron(III) compounds as long as they are uniformly soluble in ethylene glycol.

[0038] Ethylene glycol is a type of organic compound called polyol, which has multiple OH groups in its structure. Polyols are used in the synthesis of metal fine particles (polyol method) and play two roles: a solvent and a reducing agent. In this embodiment, ethylene glycol also acts as a solvent that dissolves iron chloride (III) and at the same time as a reducing agent that reduces a part of Fe (III) to Fe (II). In addition to ethylene glycol, polyols that are liquid at room temperature, such as diethylene glycol, triethylene glycol, 1,2-propanediol, and 1,3-propanediol, can be used, but these cannot be used alone and are mixed with ethylene glycol in any ratio.

[0039] Fe3O4 is an iron oxide containing Fe(II) and Fe(III) in a molar ratio of 1:2. When ethylene glycol and iron(III) chloride are used to obtain Fe3O4, the reducing agent ethylene glycol reduces part of Fe(III) to Fe(II), resulting in the production of Fe3O4. Therefore, the concentration of iron(III) chloride in ethylene glycol, which is both a solvent and a reducing agent, is important. The concentration of iron(III) chloride is preferably 0.05M or more and 0.2M or less, more preferably 0.1M or more. If the concentration of iron(III) chloride is less than 0.05M, that is, if the reducing agent ethylene glycol is in excess relative to Fe(III), the reduction of Fe(III) is promoted, Fe(II) increases, and Fe3O4 is not produced. On the other hand, if the concentration of iron(III) chloride exceeds 0.2M, the viscosity of the mixture increases if the concentration of the precipitant is increased to match the concentration of iron(III) chloride. This makes it difficult to prepare a uniform mixture. In addition, since convection is unlikely to occur in the mixed liquid, the mixed liquid is unlikely to be heated uniformly.

[0040] Here, the method for producing magnetic particles according to the present embodiment will be described as a method for producing magnetic particles including secondary particles formed by aggregation of a plurality of primary particles, comprising a step of obtaining an iron (III)-containing solution, a step of aging the iron (III)-containing solution, a step of obtaining a mixed solution by mixing the iron (III)-containing solution obtained in the aging step with a precipitant, and a step of heating the mixed solution. In the method for producing magnetic particles according to the present embodiment, the iron (III)-containing solution obtained in the step of obtaining the iron (III)-containing solution may contain ethylene glycol and iron (III) chloride anhydride. In addition, in the method for producing magnetic particles according to the present embodiment, the iron (III)-containing solution obtained in the step of obtaining the iron (III)-containing solution may contain ethylene glycol, iron (III) chloride anhydride, and externally added water. In addition, in the method for producing magnetic particles according to the present embodiment, the iron (III)-containing solution obtained in the step of obtaining the iron (III)-containing solution may contain ethylene glycol, iron (III) chloride anhydride, and iron (III) chloride hexahydrate. In addition, in the method for producing magnetic particles according to this embodiment, the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution may contain ethylene glycol, iron(III) chloride hexahydrate, and externally added water.

[0041] <Step of obtaining mixed liquid> The method for producing magnetic particles according to the present embodiment includes a step of obtaining a mixed solution by mixing an iron (III)-containing solution and a precipitant. When the method for producing magnetic particles according to the present embodiment includes an aging step, the method includes a step of obtaining a mixed solution by mixing the iron (III)-containing solution obtained in the aging step and a precipitant. When a precipitant is added to the iron (III)-containing solution, precursor particles are precipitated. The dispersion in which the precursor particles are dispersed is called a mixed solution. The precursor particles are particles of an amorphous and water-soluble iron (III) compound. In the method for producing magnetic particles according to the present embodiment, the precipitant is preferably an acetate. Specifically, urea, an alkali metal hydroxide, and an acetate can be used as the precipitant, but acetates such as sodium acetate, potassium acetate, and ammonium acetate are particularly preferred.

[0042] <Water in the mixture> In the method for producing magnetic particles according to the present embodiment, water derived from at least one of iron(III) chloride hexahydrate and externally added water is added in at least one of the steps of obtaining the iron(III)-containing solution and obtaining the mixed solution. Water can be added to the mixed solution. The presence of water in the mixed solution affects the primary particle size and shape of the Fe3O4 clusters that are generated. Water may be added to ethylene glycol before dissolving the iron(III) compound, to the iron(III)-containing solution, or to the mixed solution after adding the precipitant.

[0043] The water in the mixture may be hydrated water of hydrates such as iron(III) chloride hexahydrate and water that is intentionally added (hereinafter also referred to as "externally added water"). It is necessary that water originates from at least one of iron(III) chloride hexahydrate and externally added water exists. When no water exists in the mixture, for example, when the iron(III) compound is iron(III) chloride anhydride, heating a mixture of ethylene glycol, iron(III) chloride anhydride, and sodium acetate produces Fe3O4 clusters with small primary particle size, but these clusters deform or bond together.

[0044] When the molar ratio of iron(III) chloride anhydride to iron(III) chloride hexahydrate is changed while keeping the iron(III) chloride concentration constant, as the ratio of iron(III) chloride hexahydrate increases, that is, as the amount of water in the mixed solution increases, the primary particle size of the Fe3O4 clusters increases, but the shape becomes spherical as deformation and adhesion are suppressed. Also, when external water is intentionally added to a mixed solution of ethylene glycol and iron(III) chloride anhydride, the primary particle size of the Fe3O4 clusters increases and the secondary particles become spherical as described above with increasing amount of external water added.

[0045] The primary particle size of Fe3O4 clusters increases with an increase in the amount of water in the mixed solution. This is presumably because the solubility of Fe3O4 in water is higher than that in ethylene glycol, and therefore the presence of water in the mixed solution reduces the degree of supersaturation of Fe3O4 and the number of nuclei generated. On the other hand, the shape of Fe3O4 clusters is thought to be affected by the interfacial free energy between Fe3O4 and the solvent. Since the interfacial free energy between Fe3O4 and ethylene glycol is different from the interfacial free energy between Fe3O4 and the ethylene glycol / water mixed solvent, the shape of Fe3O4 clusters is thought to change depending on the presence or absence of water in the mixed solution.

[0046] In the method for producing magnetic particles according to the present embodiment, the amount of water per 30 mL of ethylene glycol in the iron (III)-containing solution is preferably more than 0 mL and less than 10.0 mL, more preferably 0.2 mL or more and less than 8.0 mL. If no water is contained, there is no effect on spheroidization of Fe3O4 clusters. If the amount of water is more than 10.0 mL, the primary particles of Fe3O4 do not form clusters. As described above, the primary particles of Fe3O4 clusters become larger with an increase in the amount of water, but if the amount of water is 8.0 mL or less, the increase in the size of the primary particles can be suppressed by combining it with operations such as adding additives, stirring during heating, and aging, which will be described later. In addition, if the amount of water is more than 10.0 mL, Fe2O3 is generated in addition to Fe3O4. The amount of water per 30 mL of ethylene glycol is the sum of the hydration water of the hydrate and the water added externally. For example, if 0.9 mmol of iron(III) chloride anhydrous and 3.6 mmol of iron(III) chloride hexahydrate are dissolved in 30 mL of ethylene glycol and 0.4 mL of external water is added, the amount of water of hydration contained in 3.6 mmol of iron(III) chloride hexahydrate is 0.39 mL, so the amount of water per 30 mL of ethylene glycol is 0.79 mL.

[0047] <Additives in the mixture> Additives may be added to the mixture to reduce the particle size of the primary particles that constitute the Fe3O4 clusters and to improve the dispersibility of the Fe3O4 clusters. Examples of additives that can be used include polymer compounds, low molecular weight compounds, surfactants, and chelating agents. Additives that can be added to the mixture include carboxylate ions (-COO - It is preferable that the additive has a group which becomes a carboxylate ion (-COO - ) strongly coordinates with Fe(III), so it is possible to control the growth rate of primary particles of Fe3O4. - As the additive having a group which becomes ), a carboxylic acid or a carboxylate can be used, but a carboxylate having a high degree of dissociation and which easily generates a carboxylate ion is preferably used. Specifically, citric acid, malic acid, acrylic acid, tartaric acid, lactic acid, oleic acid, succinic acid, maleic acid, fumaric acid, and alkali metal salts thereof are preferred, and trisodium citrate and sodium acrylate are particularly preferred.

[0048] These additives not only reduce the size of the primary particles of the Fe3O4 clusters, but also have the effect of making the Fe3O4 clusters spherical as mentioned above. In other words, even if there is no water in the mixed liquid, spherical Fe3O4 clusters can be obtained if the additives coexist. These additives also have the effect of reducing the size of the secondary particles.

[0049] <Process of heating the mixed liquid> The method for producing magnetic particles according to this embodiment includes a step of heating the mixture. The mixture is heated to a temperature of 160°C or more and 240°C or less, and preferably 180°C or more and 220°C or less. If the heating temperature is less than 160°C, Fe3O4 is not produced. On the other hand, if the heating temperature exceeds 240°C, the reaction rate is high and the particle size distribution of the Fe3O4 clusters becomes large.

[0050] The heating time of the mixture is 2 to 24 hours, preferably 4 to 12 hours. If the heating time is less than 2 hours, the conversion of the precursor particles to Fe3O4 clusters is not completed, and if the heating time exceeds 24 hours, the primary particle size of the Fe3O4 clusters increases due to Ostwald ripening.

[0051] The mixed liquid may contain components whose boiling points are equal to or lower than the heating temperature, such as ethylene glycol, which has a boiling point of 197° C., or water, which has a boiling point of 100° C. Therefore, it is preferable to heat the mixed liquid using a pressure-resistant sealed container generally called an "autoclave."

[0052] The mixture may also be heated under stirring conditions using a container equipped with a stirring function. In the case of heating under stationary conditions using the above-mentioned sealed container, a concentration gradient occurs in the mixture as the reaction proceeds, and the mixture becomes non-uniform. On the other hand, in the case of heating under stirring conditions, mass transfer is promoted and the mixture can always be maintained in a uniform state, which is effective in reducing the particle size of the primary particles.

[0053] After heating, the container is left at room temperature until it cools sufficiently, and then the contents are removed. The obtained Fe3O4 clusters are washed twice with ethanol and twice with water, and then dried in a dry oven at 80°C.

[0054] <Step of Aging the Iron(III)-Containing Solution> The method for producing magnetic particles according to this embodiment may include a step of aging the iron(III)-containing solution. The iron(III)-containing solution is a homogeneous solution in which the iron(III) compound is completely dissolved in ethylene glycol. Aging is an operation of holding the iron(III)-containing solution at a constant temperature for a certain period of time.

[0055] It is speculated that aging changes the solvation state of Fe(III), for example by promoting the exchange reaction of Fe(III) ligands from chloride ions to ethylene glycol, which affects the structure of the final product, Fe3O4 clusters. In addition, although the iron(III) compounds appear to be completely dissolved macroscopically, they are dispersed in ethylene glycol in a sort of oligomer-like state microscopically, and aging causes the oligomers to become monomers, increasing the activity of the dissolved species of Fe(III), which is thought to result in changes in the primary and secondary particle sizes of the Fe3O4 clusters.

[0056] Thus, since aging is related to the dissolved species of Fe(III), it is essential that aging be performed before adding a precipitant to the iron(III)-containing solution. The structure of the Fe3O4 clusters does not change even if aging is performed after adding a precipitant to the iron(III)-containing solution and generating precursor particles.

[0057] As the aging temperature increases and as the aging time increases, the primary particle size of the Fe3O4 cluster decreases and the secondary particle size increases. In the manufacturing method of the magnetic particles according to this embodiment, the aging temperature in the aging step is preferably 0°C or more and 130°C or less, more preferably 10°C or more and 130°C or less. If the aging temperature is less than 0°C, the effect of aging is small, and if it exceeds 130°C, the primary particles of Fe3O4 aggregate in an indefinite shape and do not form spherical secondary particles. In the manufacturing method of the magnetic particles according to this embodiment, the aging time in the aging step is preferably 1 hour or more and 500 hours or less, more preferably 1 hour or more and 200 hours or less. Aging for less than 1 hour does not change the structure of the Fe3O4 cluster, and aging for more than 500 hours is excessive because the effect is saturated at a certain time.

[0058] When aging iron(III)-containing solutions, the timing of adding additives that affect the primary and secondary particle sizes of Fe3O4 clusters is also important. Even if the type and concentration of additives are the same, the secondary particle size in particular changes dramatically depending on the timing of additive addition.

[0059] When an additive is added to an iron(III)-containing solution after aging, the effect of the additive in reducing particle size is enhanced, and the secondary particle size is smaller than when the additive is added to an iron(III)-containing solution without aging. On the other hand, when an additive is added to an iron(III)-containing solution before aging, the effect of the additive in reducing particle size is offset by the effect of aging in increasing particle size, and the secondary particle size is larger than when the additive is added to an iron(III)-containing solution without aging.

[0060] In addition, when the concentration of the additive added to the iron(III)-containing solution before aging is low (0.01 M or less), the effect of aging on increasing the particle size is further promoted by the additive, and the secondary particles become gigantic. This is thought to be because the structure of the dissolved species of Fe(III) changes due to aging in the presence of the additive.

[0061] As mentioned above, the secondary particle size of Fe3O4 clusters obtained using an aged iron(III)-containing solution depends on the degree of aging. Secondary particles of 500 nm to 3000 nm can be produced. By mixing two or more iron(III)-containing solutions with different degrees of aging in any ratio, the secondary particle size of Fe3O4 clusters can be controlled. This method of controlling the particle size of Fe3O4 clusters is called the blending method. The synthesis flow of Fe3O4 clusters using the blending method is shown in Figure 4.

[0062] For example, when a weakly aged iron(III)-containing solution and a strongly aged iron(III)-containing solution are respectively an iron(III)-containing solution with a short aging time that yields Fe3O4 clusters with a particle size of 500 nm and an iron(III)-containing solution with a long aging time that yields Fe3O4 clusters with a particle size of 1000 nm, if these are mixed and used in any ratio, the particle size of the generated Fe3O4 clusters can be controlled within the range of 500 nm or more and 1000 nm or less.

[0063] <Method for identifying the product> The product was identified by X-ray diffraction measurement (XRD). XRD was performed using an X’PertPro manufactured by Spectris, under the conditions of θ-2θ scanning, tube voltage 40 kV, tube current 45 mA, scanning angle 10~70°, step 0.02°, and measurement time / step 1 sec.

[0064] <Method for measuring the primary particle size of Fe3O4 clusters> The primary particle size of the Fe3O4 clusters was measured by scanning electron microscope measurement (SEM) or XRD. For SEM, an S-4800 manufactured by Hitachi High-Technologies was used, and the measurement was performed under the conditions of acceleration voltage 5 kV and irradiation current 10 μA. Using an SEM image at a magnification of 100,000 times, the particle sizes of 50 primary particles arbitrarily extracted from the image were measured, and their average value was calculated.

[0065] For XRD, an X’PertPro manufactured by Spectris was used, and θ-2θ scanning was performed under the conditions of tube voltage 40 kV, tube current 45 mA, scanning angle 33~38°, step 0.01°, and measurement time / step 2 sec. The particle size Dnm of the primary particles was calculated using Scherrer's formula (1). D = Kλ / βcosθ (1) Here, K is the Scherrer constant (K = 0.89), λ is the wavelength of the X-ray (λ = 0.1542 nm), β is the half-width rad of the diffraction peak of the (311) plane of Fe3O4, and θ is the Bragg angle (0.3091 rad).

[0066] <Method for measuring the secondary particle size of Fe3O4 clusters> The secondary particle size of the Fe3O4 clusters was measured using SEM or dynamic light scattering (DLS). SEM was performed using the aforementioned apparatus and conditions. Using SEM images at a magnification of 10,000 times, the particle sizes of 50 randomly extracted secondary particles were measured from the images, and their average value was calculated.

[0067] Using a laser diffraction / scattering particle size distribution measuring device Partica LA-950 manufactured by Horiba, Ltd., the particle size distribution of the Fe3O4 clusters was obtained by DLS. The median diameters D50 and D90 calculated from the measured number-based particle size distribution were calculated.

[0068] <Method for Measuring Magnetic Properties of Fe3O4 Clusters> The magnetic properties of the Fe3O4 clusters were measured using a magnetic property measurement system MPMS3 manufactured by Quantum Design at a measurement temperature of 298 K, in VSM mode, and in a magnetic field range of -20,000 to +20,000 Oe to measure the hysteresis curve.

[0069] <Preparation of Magnetic Particles for Assay> Note that the Fe3O4 clusters generated with controlled particle sizes can be used as magnetic particles for assay by further forming an inorganic layer or an organic layer on the particle surface. As magnetic particles for assay, first, in order to ensure the surface smoothness of the Fe3O4 clusters, a silica layer may be formed by a wet method such as the Stоber method. Then, it is preferable to form a styrene-based resin layer with high chemical stability and hydrophobicity as the first resin layer, and further form a polyglycidyl methacrylate layer as the second resin layer. The second resin layer preferably allows a ligand to bind to its surface, and the ligand is preferably an antibody. As functional groups for binding an antibody to the outermost surface of the magnetic particles for assay, carboxyl groups, amino groups, thiol groups, epoxy groups, etc. are suitable, so the second resin layer is preferably a resin containing these functional groups.

[0070] The magnetic particles for assay may further contain a fluorescent material. There is no limitation on the method of applying the fluorescent material, and any known technology may be selected. The timing of applying the fluorescent material may be, for example, when the silica layer is formed, or the silica layer is formed and the fluorescent material is applied before the first resin layer is formed, or the fluorescent material may be mixed together when the first resin layer is formed, or the first resin layer is formed and the fluorescent material is applied before the second resin layer is formed, or the fluorescent material may be applied after the second resin layer is formed. The method of applying the fluorescent material may be achieved, for example, by mixing the fluorescent material and an organic solvent after forming the resin layer and stirring while heating, or by mixing the fluorescent material together when forming the resin layer. There is no limitation on the fluorescent material to be selected, and any known fluorescent material may be selected. The fluorescent material may be either non-polymerizable or polymerizable. Examples of non-polymerizable fluorescent materials include rhodamine B, rhodamine 6G, and europium complexes such as Lumesis (registered trademark) E-400 and Lumesis (registered trademark) E-460. Examples of polymerizable fluorescent materials include acryloxyethyl thiocarbamoyl rhodamine B and methacryloxyethyl thiocarbamoyl rhodamine B. EXAMPLES

[0071] The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples. The production conditions and results of the Fe3O4 clusters in the examples are summarized in Table 1.

[0072] <Synthesis of Fe3O4 cluster> <Example 1> A 0.15 M solution of iron(III) chloride in ethylene glycol (iron(III)-containing solution) was prepared by dissolving 4.5 mmol of anhydrous iron(III) chloride (FeCl3; Kishida Chemical Co., Ltd.) in 30 mL of ethylene glycol (dehydrated; Fujifilm Wako Pure Chemical Industries, Ltd.).

[0073] After adding 0.4 mL of externally added H2O to this iron (III)-containing solution, aging was performed. The aging temperature was 25°C, and the aging time was 72 hours. The aging was performed by pouring the iron (III)-containing solution into a pressure-resistant container equipped with a Teflon (registered trademark) inner cylinder, sealing it, and then placing it in an incubator. 2.7 g of sodium acetate (CH3COONa; Kishida Chemical Co., Ltd.) was added to the iron (III)-containing solution after aging to obtain a mixed solution in which precursor particles were dispersed. This mixed solution was poured into a pressure-resistant container equipped with a Teflon (registered trademark) inner cylinder, sealing it. The pressure-resistant container was heated in an oven at 180°C for 12 hours. After the reaction was completed, the pressure-resistant container was sufficiently cooled to near room temperature, and the generated Fe3O4 clusters were taken out. The obtained Fe3O4 clusters were washed twice each with ethanol and water, and dried in an oven at 80°C. SEM images of the generated Fe3O4 clusters are shown in Figures 5(a) and 5(b).

[0074] <Example 2> Magnetic particles were produced in the same manner as in Example 1, except that the aging temperature of the iron(III)-containing solution was 60° C. and the aging time was 72 hours. SEM images of the generated Fe3O4 clusters are shown in Figures 6(a) and 6(b).

[0075] <Example 3> Magnetic particles were prepared in the same manner as in Example 1, except that the aging temperature of the iron (III)-containing solution was 100° C. and the aging time was 72 hours.

[0076] <Example 4> Magnetic particles were prepared in the same manner as in Example 1, except that the aging temperature of the iron (III)-containing solution was 60° C. and the aging time was 24 hours.

[0077] <Example 5> Magnetic particles were prepared in the same manner as in Example 1, except that the aging temperature of the iron (III)-containing solution was 60° C. and the aging time was 120 hours.

[0078] <Example 6> Magnetic particles were produced in the same manner as in Example 1, except that the aging temperature of the iron(III)-containing solution was 60° C. and the aging time was 168 hours. SEM images of the generated Fe3O4 clusters are shown in Figures 7(a) and 7(b).

[0079] <Example 7> In Example 1, the aging temperature of the iron (III)-containing solution was 60° C., and the aging time was 168 hours. Trisodium citrate was added to the iron (III)-containing solution after aging to a concentration of 0.01 M. Other than these conditions, magnetic particles were produced in the same manner as in Example 1.

[0080] <Example 8> In Example 1, a solution in which 0.9 mmol of FeCl3 and 3.6 mmol of FeCl3·6H2O were dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1. SEM images of the generated Fe3O4 clusters are shown in Figures 8(a) and 8(b).

[0081] <Example 9> In Example 1, a solution in which 0.9 mmol of FeCl3 and 3.6 mmol of FeCl3·6H2O were dissolved in ethylene glycol was used as the iron(III)-containing solution. The aging temperature of the iron(III)-containing solution was 25°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0082] <Example 10> In Example 1, a solution in which 0.9 mmol of FeCl3 and 3.6 mmol of FeCl3·6H2O were dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Trisodium citrate was added to the iron(III)-containing solution after aging to a concentration of 0.01 M. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0083] <Example 11> In Example 1, a solution in which 3.6 mmol of FeCl3 and 0.9 mmol of FeCl3·6H2O were dissolved in ethylene glycol was used as the iron(III)-containing solution. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Sodium acrylate was added to the iron(III)-containing solution after aging to a concentration of 0.01 M. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0084] <Example 12> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0085] <Example 13> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced in the same manner as in Example 1.

[0086] <Example 14> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. Sodium acrylate was added to the iron(III)-containing solution before aging to a concentration of 0.01 M. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1. SEM images of the generated Fe3O4 clusters are shown in Figures 9(a) and 9(b).

[0087] <Example 15> In Example 1, the aging temperature of the iron (III)-containing solution was 60°C, and the aging time was 168 hours. The mixed solution was heated under stirring conditions using a flask and a mechanical stirrer. Other than these conditions, magnetic particles were produced in the same manner as in Example 1.

[0088] <Example 16> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. Disodium malate was added to the iron(III)-containing solution before aging to a concentration of 0.01 M. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0089] <Example 17> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. Disodium malate was added to the iron(III)-containing solution before aging to a concentration of 0.08 M. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0090] <Example 18> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. Sodium oleate was added to the iron(III)-containing solution before aging to a concentration of 0.01 M. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0091] <Example 19> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. Sodium oleate was added to the iron(III)-containing solution before aging to a concentration of 0.08 M. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0092] <Example 20> In Example 1, sodium acrylate was added to the iron (III)-containing solution before aging to a concentration of 0.04 M. The aging temperature of the iron (III)-containing solution was 60° C., and the aging time was 168 hours. Other than these conditions, magnetic particles were produced in the same manner as in Example 1.

[0093] <Example 21> In Example 1, the aging temperature of the iron (III)-containing solution was 60° C., and the aging time was 168 hours. Sodium acrylate was added to the iron (III)-containing solution after aging to a concentration of 0.04 M. Other than these conditions, magnetic particles were produced in the same manner as in Example 1.

[0094] <Examples 22 to 29> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in ethylene glycol was used as the iron(III)-containing solution. The amount of externally added H2O was 0 mL. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 4 to 168 hours. Other than these conditions, magnetic particles were produced in the same manner as in Example 1. For Examples 22 to 29, SEM images of the generated Fe3O4 clusters are shown in Figures 10(a) to 10(h).

[0095] <Comparative Example 1> Magnetic particles were prepared in the same manner as in Example 1, except that the iron (III)-containing solution was not aged.

[0096] <Comparative Example 2> Magnetic particles were produced in the same manner as in Example 1, except that the amount of externally added H2O was 0 mL. SEM images of the generated Fe3O4 clusters are shown in Figures 11(a) and 11(b).

[0097] <Comparative Example 3> In Example 1, the amount of externally added H2O was 8.5 mL. The aging temperature of the iron (III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced in the same procedure as in Example 1. SEM images of the generated Fe3O4 clusters are shown in Figures 12(a) and 12(b). The formation of Fe3O4 clusters could not be confirmed.

[0098] <Comparative Example 4> Magnetic particles were prepared in the same manner as in Example 1, except that the aging temperature of the iron (III)-containing solution was set to 140°C.

[0099] <Comparative Example 5> In Example 1, a solution in which 4.5 mmol of FeCl3·6H2O was dissolved in 1,2-propanediol (Kishida Chemical Co., Ltd.) was used as the iron(III)-containing solution. The aging temperature of the iron(III)-containing solution was 60°C, and the aging time was 168 hours. Other than these conditions, magnetic particles were produced using the same procedure as in Example 1.

[0100] <Comparative Example 6> In Example 1, the iron (III)-containing solution was not aged. The mixed solution was heated under stirring conditions using a flask and a mechanical stirrer. Other than these conditions, magnetic particles were produced in the same manner as in Example 1.

[0101] <Particle size control of Fe3O4 clusters by blending method> <Examples 30 to 32> Solution A (weak aging solution) was prepared by dissolving iron(III) chloride hexahydrate in ethylene glycol to give a 0.15 M iron(III)-containing solution, and solution B (strong aging solution) was prepared by aging a 0.15 M iron(III)-containing solution in ethylene glycol to give a 0.15 M iron(III)-containing solution, by dissolving iron(III) chloride hexahydrate in ethylene glycol at 60°C for 168 hours. These solutions A and B were mixed in an arbitrary ratio to prepare 30 mL of solution C. The volume ratio of solution A:solution B was changed in the range of 100:0 to 0:100. Synthesis example 1 was the case where the volume ratio of solution A:solution B was 100:0, and synthesis example 2 was the case where the volume ratio of solution A:solution B was 0:100.

[0102] 2.7 g of CH3COONa was added to the prepared solution C to obtain a mixture in which precursor particles were dispersed. This mixture was poured into a pressure-resistant container equipped with a Teflon (registered trademark) inner cylinder and sealed. The pressure-resistant container was heated in an oven at 180°C for 12 hours. After the reaction was completed, the pressure-resistant container was sufficiently cooled to near room temperature, and the generated Fe3O4 clusters were taken out. The obtained Fe3O4 clusters were washed twice each with ethanol and water, and dried in an oven at 80°C. The production conditions and the results of the Fe3O4 clusters in the examples are summarized in Table 2. SEM images of the generated Fe3O4 clusters are shown in Figures 13(a) to 13(e).

[0103] <Identification of the product> As a result of XRD, all particles were found to be a single phase of Fe3O4. The XRD patterns of the particles produced in Examples 22, 24, 26, and 28 are shown in Figure 14.

[0104] <Measurement of magnetic properties of Fe3O4 clusters> As a result of the magnetic properties, all the particles exhibited superparamagnetic behavior without hysteresis characteristics. The hysteresis curves of Examples 22, 24, 26, and 28 are shown in FIG.

[0105] <Preparation of magnetic particles for assay> <Reference example 1> 0.5 g of the magnetic particles prepared in Example 1 was dispersed in a mixed solution of 75 mL of ethanol (Kishida Chemical) and 75 mL of pure water. Next, 1.5 mL of tetraethyl orthosilicate (Kishida Chemical) was added, and 22.5 mL of 28% ammonia water (Kishida Chemical) was added as a catalyst, and the mixture was reacted for 1.5 hours while stirring. After the reaction, the solvent was removed by centrifugation, and the magnetic particles were washed seven times with pure water to form a silica layer.

[0106] The obtained silica-coated magnetic particles were dispersed in a mixed solution of 10 mL of ethanol and 10 mL of pure water, and 100 μL of 3-methacryloxypropyltrimethoxysilane (LS-3380, Shin-Etsu Chemical Co., Ltd.) was added as a silane coupling agent and thoroughly mixed. Next, 2 mL of 28% ammonia water was added and stirred for 1.5 hours. Next, the magnetic particles were collected with a magnet, the solvent was removed, and the particles were thoroughly washed with pure water, and then 60 mL of nitrogen-bubbled pure water was added to obtain an aqueous dispersion.

[0107] Next, this dispersion was placed in a 200 mL four-neck flask, and stirred for 15 minutes while bubbling with nitrogen at a stirring speed of 200 rpm. Then, after switching from nitrogen bubbling to nitrogen flow, 50 μL of styrene (Kishida Chemical Co., Ltd.) was added to this dispersion. Next, 0.02 g of potassium persulfate (Sigma-Aldrich Co., Ltd.) was dissolved in 2 mL of pure water previously degassed by nitrogen bubbling, and 1 mL was added to the flask. Next, the mixture was heated at 35°C for 30 minutes using an oil bath, and then heated to 60°C and held for 1 hour. Next, 200 μL of glycidyl methacrylate (Kishida Chemical Co., Ltd.) was added, and the mixture was held for another 12 hours to complete the polymerization. After the polymerization was completed, the solvent was removed by centrifugation, and the mixture was thoroughly washed with pure water.

[0108] Next, 10 mg of the obtained magnetic particles were dispersed in 5 mL of pure water. Separately from this dispersion, 350 mg of mercaptosuccinic acid (Kishida Chemical) was dissolved in 5 mL of pure water, and 0.8 mL of triethylamine (Tokyo Chemical Industry) was added to adjust the pH. 1 mL of this solution was added to the particle dispersion, thoroughly stirred, and heat-treated at 60°C for 3 hours. Thereafter, the solvent was removed by centrifugation, and the mixture was thoroughly washed with pure water to obtain a dispersion of magnetic particles having a silica layer, a first resin layer, and a second resin layer.

[0109] <Reference example 2> 0.5 g of the magnetic particles prepared in Example 1 was dispersed in a mixed solution of 75 mL of ethanol and 75 mL of pure water. Next, 1.5 mL of tetraethyl orthosilicate was added, and 22.5 mL of 28% aqueous ammonia was added as a catalyst, and the mixture was reacted for 1.5 hours while stirring. After the reaction, the solvent was removed by centrifugation, and the magnetic particles were washed seven times with pure water to form a silica layer.

[0110] The obtained silica-coated magnetic particles were dispersed in a mixed solution of 10 mL of ethanol and 10 mL of pure water, and 100 μL of 3-methacryloxypropyltrimethoxysilane was added as a silane coupling agent and mixed thoroughly. Next, 2 mL of 28% ammonia water was added and stirred for 1.5 hours. Next, the magnetic particles were collected with a magnet, the solvent was removed, and the particles were thoroughly washed with pure water, and then 60 mL of nitrogen-bubbled pure water was added to obtain an aqueous dispersion.

[0111] Next, this dispersion was placed in a four-necked 200 mL flask, and stirred for 15 minutes while bubbling with nitrogen at a stirring speed of 200 rpm. After switching from nitrogen bubbling to nitrogen flow, 5 mg of europium complex Lumesis (registered trademark) E-400 (manufactured by Central Techno Co., Ltd.), 2 mg of sodium styrenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 50 μL of styrene in which 5 mg of divinylbenzene (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved were added to the dispersion.

[0112] Next, after heating at 35°C for 30 minutes using an oil bath, 1 mg of 2,2'-azobis(2-methylpropionamidine) dihydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 1 mL of pure water previously degassed by nitrogen bubbling, and 500 μL was added to the flask. The temperature was raised to 60°C and maintained for 2 hours. Subsequently, 200 μL of glycidyl methacrylate was added, and the mixture was maintained for another 12 hours to complete the polymerization. After the polymerization was completed, the solvent was removed by centrifugation, and the mixture was thoroughly washed with pure water.

[0113] Next, 10 mg of the obtained magnetic particles were dispersed in 5 mL of pure water. Separately from this dispersion, 350 mg of mercaptosuccinic acid was dissolved in 5 mL of pure water, and 0.8 mL of triethylamine was added to adjust the pH. 1 mL of this solution was added to the particle dispersion, thoroughly stirred, and heat-treated at 60°C for 3 hours. After this, the solvent was removed by centrifugation, and the mixture was thoroughly washed with pure water to obtain a dispersion of magnetic particles having a silica layer, a first resin layer containing a fluorescent material, and a second resin layer. When the obtained dispersion of magnetic particles was irradiated with a black light (manufactured by Nichia Corporation) with an excitation wavelength of 375 nm, red light emission was confirmed.

[0114] [Table 1-1] [Table 1-2]

[0115] [Table 2-1] [Table 2-2]

[0116] The disclosure of this embodiment includes the following configurations and methods. (Configuration 1) A magnetic particle including a secondary particle formed by an aggregation of a plurality of primary particles, The average particle size of the secondary particles is 500 nm or more and 5000 nm or less, The magnetic particles are characterized in that the average particle size of the primary particles is 2 nm or more and 20 nm or less. (Configuration 2) 2. The magnetic particles according to claim 1, wherein the secondary particles have an average particle size of 500 nm or more and 3000 nm or less. (Configuration 3) 3. The magnetic particles according to claim 1 or 2, wherein the secondary particles are made of Fe3O4. (Configuration 4) 4. The magnetic particles according to any one of configurations 1 to 3, wherein the secondary particles have a spherical shape. (Configuration 5) 5. The magnetic particles according to any one of configurations 1 to 4, wherein the secondary particles have a superparamagnetic property. (Configuration 6) 6. Magnetic particles for assay, comprising the magnetic particles according to any one of configurations 1 to 5 and a resin layer on the outer side of the magnetic particles. (Configuration 7) 7. The magnetic particles for assays according to claim 6, further comprising a silica layer between the magnetic particles and the resin layer. (Configuration 8) 8. The magnetic particles for assay according to claim 6 or 7, wherein the resin layer comprises at least a first resin layer and a second resin layer. (Configuration 9) 9. The magnetic particles for use in an assay according to claim 8, wherein the first resin layer is a hydrophobic resin layer. (Configuration 10) the second resin layer is disposed on the outside of the first resin layer, 10. The magnetic particles for assay according to claim 8 or 9, wherein the second resin layer is a polyglycidyl methacrylate layer. (Configuration 11) 11. The magnetic particles for assay according to any one of aspects 6 to 10, comprising a ligand bound to the surface of the resin layer. (Configuration 12) 12. The magnetic particle for use in an assay according to claim 11, wherein the ligand is an antibody. (Method 1) A method for producing magnetic particles including secondary particles formed by agglomerating a plurality of primary particles, comprising the steps of: Obtaining an iron(III)-containing solution; Aging the iron(III)-containing solution; a step of obtaining a mixed solution by mixing the iron (III)-containing solution obtained in the aging step with a precipitating agent; heating the mixture; A method for producing magnetic particles, comprising: (Method 2) A method for producing magnetic particles according to method 1, wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol and anhydrous iron(III) chloride. (Method 3) A method for producing magnetic particles according to method 1, wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol, anhydrous iron(III) chloride, and externally added water. (Method 4) A method for producing magnetic particles according to method 1, wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol, iron(III) chloride anhydrous, and iron(III) chloride hexahydrate. (Method 5) A method for producing magnetic particles according to method 1, wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol, iron(III) chloride hexahydrate, and externally added water. (Method 6) 6. The method for producing magnetic particles according to any one of Methods 1 to 5, wherein the aging time in the aging step is from 1 hour to 200 hours. (Method 7) 7. The method for producing magnetic particles according to any one of Methods 1 to 6, wherein the aging temperature in the aging step is 10° C. or higher and 130° C. or lower. (Method 8) 6. The method for producing magnetic particles according to any one of Methods 2 to 5, wherein the amount of water per 30 mL of ethylene glycol in the iron(III)-containing solution is 10.0 mL or less. (Method 9) The method for producing magnetic particles according to method 8, wherein the amount of water per 30 mL of ethylene glycol in the iron(III)-containing solution is 0.2 mL or more and 8.0 mL or less. (Method 10) 10. The method for producing magnetic particles according to any one of methods 1 to 9, wherein the precipitating agent is an acetate salt. [Industrial Applicability]

[0117] The magnetic particles according to this embodiment are superparamagnetic and have a wide range of magnetization, and therefore are expected to be useful in the biomedical field, such as immunoassays, biomolecule separation and purification, and drug delivery. [Explanation of symbols]

[0118] 11 Primary particles that form Fe3O4 clusters 12 Fe3O4 clusters consisting of multiple primary particles 31 Fe3O4 Cluster 32 Inorganic material layer 33 First resin layer 34 Second resin layer 35 Antibodies 36 Magnetic particles for assays

Claims

1. A magnetic particle including a secondary particle formed by an aggregation of a plurality of primary particles, The average particle size of the secondary particles is 500 nm or more and 5000 nm or less, The magnetic particles are characterized in that the average particle size of the primary particles is 2 nm or more and 20 nm or less.

2. The magnetic particles according to claim 1 , wherein the average particle size of the secondary particles is 500 nm or more and 3000 nm or less.

3. The secondary particles are Fe 3 O 4 The magnetic particle of claim 1 , comprising:

4. The magnetic particles according to claim 1 , wherein the secondary particles are spherical in shape.

5. The magnetic particles according to claim 1 , wherein the magnetic properties of the secondary particles are superparamagnetic.

6. 6. A magnetic particle for assay, comprising the magnetic particle according to claim 1 and a resin layer on the outside of the magnetic particle.

7. The magnetic particles for assay use according to claim 6 , which have a silica layer between the magnetic particles and the resin layer.

8. The magnetic particles for an assay according to claim 6 , wherein the resin layer comprises at least a first resin layer and a second resin layer.

9. The magnetic particles for an assay according to claim 8, wherein the first resin layer is a hydrophobic resin layer.

10. the second resin layer is disposed on the outside of the first resin layer, The magnetic particles for assay according to claim 8, wherein the second resin layer is a polyglycidyl methacrylate layer.

11. 7. The magnetic particle for use in an assay according to claim 6, comprising a ligand bound to the surface of the resin layer.

12. The magnetic particle for use in an assay according to claim 11, wherein the ligand is an antibody.

13. A method for producing magnetic particles including secondary particles formed by agglomerating a plurality of primary particles, comprising the steps of: Obtaining an iron(III)-containing solution; Aging the iron(III)-containing solution; a step of obtaining a mixed solution by mixing the iron (III)-containing solution obtained in the aging step with a precipitant; heating the mixture; A method for producing magnetic particles, comprising:

14. The method for producing magnetic particles according to claim 13 , wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol and anhydrous iron(III) chloride.

15. The method for producing magnetic particles according to claim 13 , wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol, anhydrous iron(III) chloride, and externally added water.

16. The method for producing magnetic particles according to claim 13 , wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol, iron(III) chloride anhydrous, and iron(III) chloride hexahydrate.

17. The method for producing magnetic particles according to claim 13 , wherein the iron(III)-containing solution obtained in the step of obtaining the iron(III)-containing solution contains ethylene glycol, iron(III) chloride hexahydrate, and externally added water.

18. The method for producing magnetic particles according to claim 13 , wherein the aging time in the aging step is from 1 hour to 200 hours.

19. The method for producing magnetic particles according to claim 13, wherein the aging temperature in the aging step is 10° C. or higher and 130° C. or lower.

20. The method for producing magnetic particles according to any one of claims 14 to 17, wherein the amount of water per 30 mL of ethylene glycol in the iron(III)-containing solution is 10.0 mL or less.

21. The method for producing magnetic particles according to claim 20, wherein the amount of water per 30 mL of ethylene glycol in the iron(III)-containing solution is 0.2 mL or more and 8.0 mL or less.

22. The method for producing magnetic particles according to claim 13, wherein the precipitating agent is an acetate salt.